RELIABILITY-BASED ANALYSIS AND OPTIMIZATION OF SPRING LOCKING MECHANISM - Cai DeYong; Liu FuJun; Jiao XianWei; Wei Jun (Jixie qiangdu)
According to the stochastic distribution of parameters,the reliability analysis of spring locking mechanism is carried out for helical spring by using probability theory and mathematical statistics. The optimization model of the locking mechanism spring parameters is established. Using Simulated Annealing Algorithm（ SAA）,the optimal parameters of spring are provided with the help of computer program compiled with Visual Basic language. The rationality of optimization result is verified by simulation results of the finite element model.